2018
DOI: 10.3889/oamjms.2018.131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Plaque-Induced Gingivitis in a Sample of the Adult Egyptian Population

Abstract: AIM:The aim of this cross-sectional study is recording the prevalence and evaluation of the severity of plaque-induced gingival inflammation among a sample of the adult Egyptian population.PATIENTS AND METHODS:Four hundred and twenty-five subjects in this contemplate were seen from patients visiting the diagnostic clinic at the Faculty of Dentistry, Cairo University. The gingival and plaque indices for each patient diagnosed as having plaque-induced gingivitis were recorded. The pocket depth was also measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…The objective of our study on an adult population in the north of Portugal was to determine the prevalence, extension, severity and risk factor associated with periodontal disease on Portugal, using the new classification of periodontal disease [14,15]. Our study found a prevalence of gingivitis of 26.9%, (31.3% for women versus 22% for men) a lower value compared to another Egyptian study about plaque-induced gingivitis where the prevalence was 100% [16]. The higher prevalence for women was similar to a study of Caribbean adults [17] and different from the Egyptian result, where women were less affected [16] (42.2%).…”
Section: Discussionmentioning
confidence: 62%
“…The objective of our study on an adult population in the north of Portugal was to determine the prevalence, extension, severity and risk factor associated with periodontal disease on Portugal, using the new classification of periodontal disease [14,15]. Our study found a prevalence of gingivitis of 26.9%, (31.3% for women versus 22% for men) a lower value compared to another Egyptian study about plaque-induced gingivitis where the prevalence was 100% [16]. The higher prevalence for women was similar to a study of Caribbean adults [17] and different from the Egyptian result, where women were less affected [16] (42.2%).…”
Section: Discussionmentioning
confidence: 62%
“…Diş destek dokularında yıkıma neden olmayan ve geri dönüşümlü bir hastalık olan jinjivit, populasyonun %75'in üzerinde görülme sıklığı ile dünya üzerinde en sık görülen hastalıklardan biridir. 28 Gebelik jinjiviti ise gebelikte %30-100'ü arasında de-ğişen sıklıkta görülmektedir. 29 klinik sonuçların günlük yaşama olan etkisini göstermek ve hastanın tedavi sonuçlarına ilişkin algısını değerlendirmektir.…”
Section: Discussionunclassified
“…As large population has a mild, reversible gingivitis. Severe gingivitis is relatively rare in children [19,20]. Gingivitis is a reversible condition clinical signs such as swollen gums, bright red or purple gums, gums that are tender or painful to the touch, bleeding gums or bleeding…”
Section: Introductionmentioning
confidence: 99%